Sustainable industry according to the sustainability accounting standard (for gas utilities and distributors) IF-GU-240a2 standard and its impact on product costs (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to shed light on sustainability accounting and the most important standards issued by the Sustainability Accounting Standards Board (SASB) and to study and analyze how sustainability accounting standards (gas utilities and distributors) reflect on product costs; The research problem was represented by the inadequacy of disclosures about contributions related to pollutants, emissions and savings provided by the research sample, and measuring their costs in economic, environmental and social aspects. Therefore, the reports of economic units in general and the research sample in particular did not meet the needs of users and did not help in achieving accountability, in addition to not achieving sufficient disclosure of sustainable development goals; The research relied on data collection and analysis tools represented by financial data, reports, publications, laws and instructions for the years (2014-2020) to obtain information. The research reached a set of results, the most prominent of which was the lack of the local environment to use sustainability accounting standards, indicators and measures in the field of industries, which led to the delay of the industrial sector in disclosing financial and non-financial information, and that adopting initial indicators and measures is a first step to enhance the reality of industries, which would improve the reality of economic units in terms of making decisions based on essential information that is reflected in the environmental, economic and social aspects as a whole, and the increase in impurities during the years (2019, 2020); as it reached (109993, 125979) tons, respectively, which affects the weight to be received from the consumer, in addition to the increase in the production of filled cylinders during the coming years, which indicates the existence of costs that do not add value to the product; It amounted to (48462104311) dinars and (55634277598) dinars during the years (2019, 2020).